Study of knowledge, attitude and practice of family planning in an urban area of Bharatpur - Manandhar, N; Singh, SK; Patowary, S; Krishna, G (Journal of Institute of Medicine Nepal, 2007)
Background: A cross-sectional study was conducted during September-October, 2004 among 255 purposively selected woman of reproductive age group (15-44 years) in Bharatpur Municipality, Chitwan district. Material and Methods: Door to door survey was conducted and informations were collected on a structured and pre-tested proforma from255married women. Result: It was found that 100% of the respondents had heard about any one or the other method of family planning. All respondents had knowledge about Condom. The majority of them had knowledge about Oral Contraceptive Pills (92.9%), injectable (89.4%) and Intra Uterine Device (89.4%). The currently married women (45.8%) were using injectable (Depo-Provera). The OCP&IUD were being used by 18.8% each. Conclusion: Knowledge regarding family planning method was far from satisfactory. They had positive attitude towards family planning. Key words: Reproductive age, Contraceptive, Fertility, Woman. The full text of this paper is available at Journal of Institute of Medicine website